Highly efficient beam splitter based on all-dielectric metasurfaces. (5th June 2019) - Lin, Yu; Wang, Miao; Sui, Zhanpeng; Zeng, Zhongming; Jiang, Chunping
Abstract: The recent exploration of metasurfaces reveals potential for developing virtually flat optics. In this work, a highly efficient beam splitter based on all-dielectric metasurfaces is demonstrated for visible light by finite-difference-time-domain simulations. The structure consists of a TiO2 nano-cylinder array and a layer-by-layer reflector with high efficiency separated by a SiO2 spacer. A conversion efficiency higher than 90% can be readily achieved over a wavelength range from 490 to 560 nm for the proposed device.